Effect of different pruning date and severity on growth, yield and quality parameters of Ber (Zizyphus mauritiana Lamk) in arid condition (Indian Journal of Arid Horticulture, 2025)
The research was carded out at experimental field of Agricultural Research Stadon. Manclor. Joclhpur during April. 2016 to February. 2017 to evaluate the response of pruning time and severity on fmit production. quality and profit.ability of Ber cv. Gola. Six ye..v old grafted U'ees of ber were pnmed al intervals. i.e. on 30 April. 15 May. 30 1'.•1ay, 15 June with two pruning severity levels i.e. 30 per cem and 50 per cent removal of previous season growth. l1le yield impl'oving growlh parameters viz .. comparath•ely Je.ss number of ma.in shoots (21.43 plant'1). maximum number of btanche.s (240.25 planf1). minimum shoOl h::ngth (I 17.60 cm} and girth of shoots ( 13.26 cm) have be.ell markedly promoted by the 15th June pruning with 30 per c.en1 severity th::in 1-e.1;1 of the tl'ea1ments. Eal'ly pruning (30 ApriJ) with hjghest severity (50%) has been found to increase the vegerntive growth like shoo1 length and girth but yielrl has been formed inversely proportional supra-op1imal Jevel of pnining. Flowering and fruit sening: was delay by J 5 days in tree pn.mcd on t5'h Jtane., which was significan1ly rcdtice tlower and fruit drop. AJI 1he yield p;\ramcter aud fruit yield viz., fruit set per cent (29.40%). fruit retention per cenl (29.95%). fn1i1 harveSl per cenl (8.80%), number of fn1j1s in sq. meter 1 canopy of plant ( l65), fruit yield planf1 (72.09 kg) and fmit yield ha·' (200.41 q) was significantly higher in Ts lrcalment. Highest economic performance viz .. Gross relurn (Rs. 180368.85). nel return (Rs. 134368.5 I) and B : C nlljo (2.92) was recorded maximum in trees pnmed on I 5111 June with 30 per cent severity whereas quality charactl'!rs of fmits like highest Total Soluble Solids ( 15.4008rix ). lowest acidity (0. l 3%). high ascorbic acid (61.4 l mg 100g'1• highest fruit surface colour score (8.43). fn1it rnste score (8.20) and overall quality score of fruits (8. 76) was reported in ·r2 treatmenl. Minimum fniil Oy infC$la1io1l (3.93%) was J'cported in TI) lJ'eatmeJ\1.
Keywords: Ber; Day After Pruning; fruit set; shams